2000
DOI: 10.1039/a908984e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coordinative exchange in rhodium(I) complexes of chiral diphosphines bearing pendant pyridyl donor groups

Abstract: meso-{Ph 2 PCH(Ph)CH(Ph)PPh 2 }, meso-{Ph 2 PCH(pyr)CH(pyr)PPh 2 }, erythro-{Ph 2 PCH(Ph)CH(pyr)PPh 2 }, rac-{Ph 2 PCH(pyr)CH(pyr)PPh 2 }, threo-{Ph 2 PCH(Ph)CH(pyr)PPh 2 }, and threo-{Ph 2 PCH(Ph)CH(pym)PPh 2 }, [pyr = 2-pyridyl, pym = 2-pyrimidyl] reacted with [Rh(COD)Cl] 2 (COD = 1,5-cyclooctadiene) to give cationic rhodium() complexes [Rh(COD){L}] ϩ (L = diphosphine ligand), which were isolated as their PF 6Ϫ salts, 1-6 respectively. In 2 and in 3 the phosphine ligand adopts a P,PЈ,N-coordination mode whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The use of weakly bonded olefins as leaving groups is wide‐spread for rhodium catalysts 26. The M–C distances in 1 and 14 are located within the typical range of 2.1–2.3 Å 15,17,18,27. However, the significantly longer mean value of the M–centroid distances in 1 than in 14 nicely corresponds to the fact that cod is easily displaced in the case of 1 , whereas difficulties appear using 14 as a precursor complex as a result of the five‐coordinate species that still contains cod.…”
Section: Resultsmentioning
confidence: 99%
“…The use of weakly bonded olefins as leaving groups is wide‐spread for rhodium catalysts 26. The M–C distances in 1 and 14 are located within the typical range of 2.1–2.3 Å 15,17,18,27. However, the significantly longer mean value of the M–centroid distances in 1 than in 14 nicely corresponds to the fact that cod is easily displaced in the case of 1 , whereas difficulties appear using 14 as a precursor complex as a result of the five‐coordinate species that still contains cod.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is considerable current interest in hybrid P/N ligands and a search in the Cambridge Structure Database revealed that although a vast number of Groups 9-10 complexes with nitrogen and phosphorus ligands have been characterised structurally, only a relatively small number of Pd(II) cations and Rh(I) cations [54][55][56][57][58][59][60][61][62][63][64][65] containing bidentate N(sp 2 )-P(sp 3 ) donors are reported. Since bulky substituents at the aryl groups of N(sp 2 ) donors have been found to strongly influence the catalytic activity and selectivity of Group 10 complexes [66], it is surprising that no Rh(I) complexes of ligands combining tertiary phosphine donors and (sp 2 )N-aryl donors with bulky ortho substituents have been structurally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…shows a similar P,P',N and P,P',N' exchange for a Rh(I) complex. 22 Also notable is the behavior of It has been reported that rhodium catalysts containing achiral -aminophosphines have a greater activity when the ligand bears an ether vs an alcohol function. 8 The preparation of a P,N,N ligand with a chiral -amino-phosphine moiety has not so far been considered.…”
Section: Introductionmentioning
confidence: 99%